Enhancing the Capacity of Women-Based Microfinance Groups in Margamulya Village, Lebak Regency - Husain, Muhammad Kamil; Wijaya, Herman; Maulana, Delly (Universitas Serang Raya, 2025)
A women's community in Margamulya village, Cileles district, Lebak Regency, is a Women-Based Microfinance Group (KKMBP) forum member. This group receives capital assistance from zakat funds for business capital, but they are often unable to return the loan because the loan funds run out for daily food costs because the business is not profitable. The main problems are: 1) lack of understanding of the status of the loan funds for members who get loans from zakat funds, and 2) the level of ability of residents to manage businesses so that the business is not profitable. Therefore, community service is needed to increase the retention and understanding of partners about the status of loan funds sourced from Zakat so that participants can increase their capacity on how to manage the trading business that has been run and how to increase business profits so that they can improve the family economy which is further avoided by loan sharks who continue to try to provide loans with a very burdensome interest burden. The result of this service is in the form of increasing residents' business capacity, as evidenced by the ability of residents to open and manage businesses in the form of two meatball stalls, two seblak stalls, and two fritter stalls. The six stalls can operate and provide benefits to residents so that they can improve the family economy.